(3fXe EOGQI GdLhOI (B:s (3aj GdefXeGJ GdEfJGLjI hGdNOejI (B/s - (3GdWGFj, jhSa MLjes; (3GdMcje, djK Ydj s; (3GdYLjdj, eMeO YGUj s ((3YeGf(B: s (3OGQ GdjGRhQj ddfTQ hGdJhRjY(B, s, 2009)
(3GdeONd GdJfXjej hGdJWhQ GdeaGgjej ddLhOI(B- (3GdQbGHI Ydi GdLhOI(B- (3MdbGJ VHW GdLhOI(B- (3EOGQI GdLhOI GdTGedI(B- (3VeGf GdLhOI(B- (3JObjb GdLhOI(B- (3fXe EOGQI hVeGf GdLhOI (BISO - (3fXe GdEOGQI GdHjFjI (B14000 ISO -(3eaGgje eYGUQI aj EOGQI GdLhOIs
Keywords: (3GdEOGQIs; (3GdEjRhs; (3VHW GdLhOIs; (3fXe GdEOGQIs